Unlocking Africa’s solar and wind energy potential: A panel data analysis on the determinants of the production of electricity through solar and wind energy - de Vries, Martina Gintarė (International Journal of Renewable Energy Development, 2023)
With growing global concerns about and attention drawn to climate change, there is a pressing need to transition towards sustainable practices to live more harmoniously with the environment. To mitigate future climate changes, many support and pursue the uptake of renewable energy to slowly shift to a more electricity powered world. Africa, richly endowed with the potential of solar and wind, stands at a pivotal point with the opportunity to develop through electricity generated by renewable. Therefore, this research delves into the complexity of 25 factors influencing the production of solar and wind-powered electricity within the continent. Through a panel data analysis conducted for the years of 2010 till 2019, the study identifies several determinants to have positive and negative effects. Results highlight the intertwined nature of regional challenges and opportunities, emphasizing that political stability, socio-economic dynamics, sound national strategies, and environmental and international commitments play pivotal roles in determining the trajectory of solar and wind energy integration in Africa’s electricity mix. Notably the study underscores that a uniform approach across Africa is insufficient, instead tailored national and foreign strategies based on regional specifics found within this study are imperative for maximizing renewable energy adoption.